Exploring Young Volunteers' Experiences in Teaching English Vocabulary to Immigrant Children in Malaysia - Achmad Ghazali Rachman; Khusnul Khatimah; Rani Herning Puspita (English Language Teaching Methodology, 2026)
Children of Indonesian migrant workers in Malaysia often face limited access to formal education due to legal and social constraints. This condition highlights the importance of non-formal education supported by young volunteers. This study explores the experiences of Indonesian young volunteers in teaching English vocabulary to immigrant children at Sekolah Indonesia Kuala Lumpur (SIKL) within a temporary learning environment. A qualitative descriptive approach was employed through semi-structured interviews with four volunteers aged 16–21 years. The data were analyzed thematically to identify volunteers’ motivations, teaching strategies, and challenges. The findings indicate that volunteers were motivated by social contribution and personal development. Game-based activities, storytelling, and simple rewards effectively increased children’s participation and engagement. However, volunteers encountered challenges related to limited facilities, physical fatigue, and classroom management. Overall, the involvement of young volunteers had a positive impact on the learning process of immigrant children and contributed to the volunteers’ social and emotional development.